DEVELOPMENT OF GLOBAL WARMING THEMED VIDEO GAMES: IMPLEMENTATION OF GAME DEVELOPMENT LIFE CYCLE (GDLC) FRAMEWORK - Tony Wibowo; Ericson Hermanto (Universitas Internasional Batam, 2022)
Video games have become a part of people’s typical livelihood. Video games can be used for various purposes, not only for entertainment, one of which is conveying messages with deep meaning. In this article, we will discuss the design and development of a video game in the form of a serious game, with the theme of global warming. This research aims to raise awareness of the environment to overcome environmental problems. The serious game was developed using the Game Development Life Cycle (GDLC) framework. We produced a video game that has the mechanics, dynamics, and aesthetics based on the game development document (GDD). The result of this study is a simulation video game that main objective is to grow trees successfully. By developing this video game, we attempting to spread the message of global warming and the cause that is deforestation to the younger generation. The following describes the process of development of the serious game.